Hepatic FOXA3 overexpression prevents Western diet–induced obesity and MASH through TGR5 - Raja Gopoju; Jiayou Wang; Xiaoli Pan; Shuwei Hu; Li Lin; Alyssa Clark; Yanyong Xu; Liya Yin; Xinwen Wang; Yanqiao Zhang (Journal of Lipid Research, 2024)
Forkhead transcription factor 3 (FOXA3) has been shown to regulate metabolism and development. Hepatic FOXA3 is reduced in obesity and fatty liver disease. However, the role of hepatic FOXA3 in regulating obesity or steatohepatitis remains to be investigated. In this work, C57BL/6 mice were i.v. injected with AAV8-ALB-FOXA3 or the control virus. The mice were then fed a chow or Western diet for 16 weeks. The role of hepatic FOXA3 in energy metabolism and steatohepatitis was investigated. Plasma bile acid composition and the role of Takeda G protein–coupled receptor 5 (TGR5) in mediating the metabolic effects of FOXA3 were determined. Overexpression of hepatic FOXA3 reduced hepatic steatosis in chow-fed mice and attenuated Western diet–induced obesity and steatohepatitis. FOXA3 induced lipolysis and inhibited hepatic genes involved in bile acid uptake, resulting in elevated plasma bile acids. The beneficial effects of hepatic FOXA3 overexpression on Western diet–induced obesity and steatohepatitis were abolished in Tgr5−/− mice. Our data demonstrate that overexpression of hepatic FOXA3 prevents Western diet–induced obesity and steatohepatitis via activation of TGR5.